Environmental Effects of Heavy Metals from the E-Waste Dismantling Site, South China. Issue 6 (18th August 2021) - Kong, Deguan; Du, Yongming; Luo, Min; Liu, Guowei; Su, Xiaotong; Luo, Dinggui; Huang, Xuexia; Wei, Lezhang; Liu, Yu; Wu, Qihang
ABSTRACT: E-waste dismantling activities have caused serious heavy metals pollution in some parts of China. In this study, the contents of 15 metals (Ag, As, Cd, Co, Cr, Cu, Li, Mn, Ni, Pb, Rb, Sb, Sn, Tl, and Zn) in soil, sediment, and water hyacinth derived from the e-waste dismantling activities were investigated. Based on these data, the Geo-accumulation index (Igeo ) and the potential ecological risk index (RI) were used to assess potential ecological risk. The results showed that the concentration of As, Cd, Cu, Sb, Sn, and Zn in soil for 6.4–131, 0.09–11.2, 25.5–5900, 3.7–443, 5.7–272, and 39–2040 mg kg −1, which the average content exceeded the natural background levels for 5.6, 57, 87, 142.7, 16.7 and 12.7 times, respectively. The concentration of Cu, Sb, Sn, and Zn in sediment for 41.2–468.3, 2.59–33.83, 10.3–92.9, and 148–502.7 mg kg −1, respectively, which the average content exceeded the natural background levels for 14.7, 20.9, 7.1, and 5.7 times, respectively. The Igeo indicated that soil and sediment at sites where e-waste was still heavily contaminated with a variety of heavy metals (such as Cd, Cu, Pb, Sb, Sn, and Zn), which were obvious accumulation effects. The RI in the surface of sediment indicated the average ecological risk of As, Cd, Co, and Cu was high risk and the total risk reached a very high risk at each sampling site. Water hyacinth has strong ability to enrich heavy metals. We suggest that the heavy metals in soil and sediment should be periodically monitored, especially Cd, Cu, Pb, Sb, Sn, and Zn. Water hyacinth can be used to monitor these heavy metals contaminated in river. The cleaning up of the soil and sediment should be a priority for any future remediation program in the study area.